DRIVERS OF IMPULSIVE FASHION PURCHASES ON TIKTOK SHOP: THE ROLE OF HEDONIC MOTIVES, LIFESTYLE, AND PROMOTIONS - Maulana, Muhammad Alfin; Nurmiyati, Nurmiyati; Rahayu, Sri (Jurnal Comparative: Ekonomi dan Bisnis, 2025)
This study examines the influence of hedonic shopping motivation, shopping lifestyle, and sales promotion on impulsive buying behavior in fashion products on TikTok Shop. Impulsive buying has become increasingly prevalent in social commerce, driven by emotional engagement and promotional stimuli. A quantitative approach was employed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS software. Data were collected from 100 active TikTok Shop users through purposive sampling. The findings reveal that hedonic shopping motivation and sales promotion have a significant positive effect on impulsive buying, confirming that emotional gratification and attractive promotional strategies strongly trigger unplanned purchases. Contrary to expectations, shopping lifestyle exhibits a negative and insignificant relationship with impulsive buying, suggesting that habitual shopping patterns may not necessarily lead to impulsive decisions in this digital context. The results highlight the critical role of experiential and promotional elements in shaping consumer behavior on short-video e-commerce platforms. This study contributes to the growing literature on digital consumer behavior by empirically validating key drivers of impulse purchases in the context of social commerce. For practitioners, the findings suggest that enhancing user experience and designing engaging promotional campaigns can effectively stimulate sales in the competitive online fashion market.